Literature and society: discursive practices in Bom-Crioulo by Adolfo Caminha - Lima, Marcos S. S. de (FCL-UNESP Laboratório Editorial, 2018)
This work presents a discursive analysis of a literary work that explores extremely current topics, such as social and especially homophobic prejudices. We will examine in particular Amaro (Bom-crioulo), Aleixo and D. Carolina, characters from the creation O Bom-Crioulo, produced in 1895 by Adolfo Caminha, one of the main Brazilian authors of the Naturalist style. Specifically, we will highlight the discourses, power relations and subjectivity of the subjects represented here by the protagonists. Finally, we will show how these concepts shape society, how subjects of a particular time period are constructed by its discursive practices and the exercise of power relations, and since these are manufactured subjects, fabricated, constructed by these discursive practices, by the constituted powers, they thus become “useful” subjects to society. Such an approach is based on theoretical concepts by Michel Pêcheux and, especially, by Michel Foucault.